Peramalan Jumlah Pengunjung Wisata Menggunakan Fuzzy Logical Relationship dan Algoritme Genetika (Studi Kasus Wisatawan Kabupaten Banyuwangi) - Irma Lailatul Khoiriyah; Imam Cholissodin; Budi Darma Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tourism is one of the important sectors in Banyuwangi Regency. An unexpected increase in the number of tourists makes it difficult for tourism department to give their best service. On the contrary, if there is a reduction, it will cause the decrease of the occupancy rate and the tourism sector that already exist. Forecasting the number of tourists is needed to determine the number of visitors in the future, so the solution can be anticipated as early as possible when number of tourists is more or less than the targeted. Forecasting that conducted in this study was using Fuzzy Logical Relationship and Genetic Algorithm. Fuzzy Logical Relationship is used to forecast the number of tourist based on tourist data history, then Genetic Algorithm is used to perform optimization interval distribution that will be used on Fuzzy Logical Relationship. Data that were used as many as 144 historical data from January 2005 to December 2016, number of tourist data was achieved from the Department of Culture and Tourism of Banyuwangi Regency. The results of the tests that was conducted on forecasting the number of visitors using the FLR and GA equations produce 280x10-9 in fitness which means the difference between the average of actual data and the result of forecasting is 3572978344 in MSE.